Gênese do processo criativo de O Bravo Guerreiro, 1969, de Gustavo Dahl : o herói atônito - Bazanini, Julio Cesar (2014)
This research aims to study the creative process of the Brazilian film “O Bravo Guerreiro” (The Brave Warrior), 1969, Gustavo Dahl, from the analysis, description and comparison of the different versions of scripts and other peripheral documents belonged to the film. These files are deposited in “Cinemateca Brasileira” and many of them have not been officially cataloged. Thus one of the efforts of this paper will be to detail them seeking reach the poetic project of the author, revealing its esthetic and ethical principles of that moment. The theoretical support offered by academics in Critics of Creative processes will be the main tool for this task. We intend to use this material, the result of the comparative reading of scripts and other documents, to understand the Brazilian political and cultural context of the late 60's, taking as basis for such work theories that allows to think the examination of film documents, in addition to film, as a source for the writing of history.